Assessments of Physical Analysis on Water Quality in Benadir Region, Somalia: Physical Analysis on Water - Abdi - Soojeede, Mohamed Ibrahim; Nour, Dayib Hashi (Integrated Journal for Research in Arts and Humanities, 2022)
Pollution is a Presence of pollutant substances in the water which are harmful to man, plants, or property, pollutants are agents that can alter the normal characteristics of water. This needs to measure the concentration of the constituents in quantity for characterization of water for different methods and instruments or various other parameters. So that the objectives were to demonstrate a physical test (TDS, EC, PH, and Turbidity) of groundwater and to determine the water quality index in Mogadishu, Somalia. Methods: The study's design is a qualitative and quantitative descriptive study that involves diagnosing or testing 30 water samples gathered from 12 districts in Mogadishu's Benadir region from April to June 2022, Data was entered into Excel, and the data was evaluated using charts, and the water quality index (WQI). Result: In TDS concentrations ranged from 180 to 2966 mg/L (parts per million). TDS of drinking water should be less than 1000 mg/L, according to WHO recommendations, and EPA secondary drinking water regulations. TDS levels of 500 ppm are regarded safe. The pH levels were discovered to range from 5.5 to 7.0. The pH of drinking water should be between 6.5 and 8.5, according to WHO recommendations. Except for 17 samples that were out of normal range. The highest acceptable conductivity level, according to WHO [6], is 300